Applied Fluid Mechanics Lab Manual - Ahmari, Habib; Md Imran Kabir, Shah (Open textbook library., 2019)
This lab manual provides students with the theory, practical applications, objectives, and laboratory procedure of ten experiments. The manual also includes educational videos showing how student should run each experiment and a workbook for organizing data collected in the lab and preparing result tables and charts.